2021
DOI: 10.1111/trf.16518
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of weakDtype 42 in a large‐scaleRHDgenotyping program in the province ofQuebec (Canada)

Abstract: Background: The determination of the RhD phenotype is crucial to avoid alloimmunization, especially in childbearing women. Following the 2015 recommendation from the Work Group on RHD Genotyping, a large-scale RHD genotyping program was implemented in the province of Quebec (Canada) and offered to women ≤45 years old with a serological weak D or discordant results. Since weak D type 42 was previously shown to be prevalent among French Canadians, genotyping for that variant was also performed. Our aim was to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Notably, 56% (15/27) of our patients with partial D variants had 3–4+ IS tube typings and would have been missed in some genotyping decision protocols. 4 , 7 , 8 RHD genotyping results changed RhIG or RBC transfusion management in 43% of our cohort. A high proportion of ethnically diverse patients and over one‐third of White patients with weak or discrepant D phenotypes had RHD genotypes warranting D‐negative management.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Notably, 56% (15/27) of our patients with partial D variants had 3–4+ IS tube typings and would have been missed in some genotyping decision protocols. 4 , 7 , 8 RHD genotyping results changed RhIG or RBC transfusion management in 43% of our cohort. A high proportion of ethnically diverse patients and over one‐third of White patients with weak or discrepant D phenotypes had RHD genotypes warranting D‐negative management.…”
Section: Discussionmentioning
confidence: 87%
“… 1 , 2 However, in automated RhD typing systems with diverse methods and reagents, there is limited disparate information on how to efficiently define weak D phenotypes needing RHD allele determination. 3 , 4 , 5 , 6 , 7 , 8 , 9 Furthermore, previously United States and Canadian studies have not prospectively examined the clinical impact of RHD genotyping on ensuing needs for D‐negative RBC transfusions. We sought to examine these issues after initiating RHD genotyping in our transfusion service.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the high prevalence of weak D type 42 in Québec does not appear to increase the overall prevalence of weak D phenotypes. Instead, other weak D phenotypes seemingly exhibit a lower prevalence that offsets the high prevalence of weak D type 42 (e.g., the prevalence of weak D type 1 among weak D phenotypes: 15.3% in the Leiva‐Torres et al study [7] and 24.9%–79.0% in other studies). These results may prove useful to conduct risk analyses that will inform the clinical management of patients with weak D phenotypes.…”
Section: Discussionmentioning
confidence: 94%
“…The epidemiology of this phenotype is, however, little documented. In a recent study conducted in Québec, 17.48% of women aged ≤45 with an atypical D typing result had weak D type 42, whereas only 15.3% had type 1, 3.3% had type 2 and 8.6% had type 3 [7]. Furthermore, Leiva‐Torres et al recently showed that the regional prevalence of weak D type 42 was negatively correlated with the proportion of minorities consistent with a founder effect [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation